Insecurity and generalized political crises - Lawali Dambo; Maman Waziri Mato; Département de Géographie; Université de Zinder; Niger; Elhadji Maman Moutari (Revue de Géographie Alpine)
The tourism model adopted by the Agadez region in Niger, which is built around a series of pioneering and sometimes unique products, has had a rough ride for two decades and today is in crisis.The region has reached an impasse as a result of a situation of generalized insecurity in the Sahel-Saharan sub-region and in northern Niger in particular. This chronic insecurity, resulting from several political crises (two rebellions in Niger, crises in Libya and Mali, the Boko Haram movement in northern Nigeria) since the 1990s, has revealed the extreme weakness of a tourism model in an area whose geopolitical situation, once considered an asset, has become a major constraint on the flowering of an activity that contributes both to the livelihood of a whole region and the cultural development of an entire people.This insecurity has obliged different local stakeholders to develop adaptation strategies ranging from the exercise of multiple activities to a sort of conversion from tourism towards other sectors of activity. The change in the economic situation has different consequences depending on the stakeholders and their level of dependence on tourism.